Species diversity and assemblage of fish fauna of Sip River: A tributary of Narmada River - Vyas, Vipin; Vishwakarma, Kripal Singh (Journal of Research in Biology, 2013)
The Sip River is a tributary of the River Narmada, joining Narmada right bank just upstream of Indira Sagar Reservoir. A systematic study of fish diversity in River Sip has been neglected and the information on this aspects in scanty, either very old or not been updated for decades. Keeping this in view, the present study was conducted. The aim of this study is to document ichthyofauna and to provide measures for their conservation. The present work was done from the period of May 2011 to April 2012. A total of 29 species belonging to 17 genera, eight families and three orders were recorded. A total of 427 individuals were caught from eight stations. The most abundant group of fish was Cyprinidae. Out of all these, Rasbora daniconius has the maximum number of individuals (116) recorded from all sites and contributes 27.16% of the total population